ANALISIS KEBUTUHAN PENGEMBANGAN PEMBELAJARAN PENULISAN NASKAH PR I - Fifit Fitriansyah (Cakrawala - Jurnal Humaniora, 2019)
Learning PR Scripts Writing I is one of the pre-eminent courses for students of public relations study programs (Public relations) at the Faculty of Communication and Language at the University of Bina Sarana Informatika, in their study introducing and providing knowledge about the skills that must be owned by Public relations in this case writing skills (writing skills). The technique of writing public relations (Public relations Writing) itself is a typical writing skill (PR skill) / PR in producing texts that are needed to build a positive image and popularity of a company or organization. The purpose of this study is to identify learning needs related to the problems in learning PR Script Writing I. The results of this study are the development of learning PR Script Writing I in accordance with learning.